Cooperative Spirits: The Seth Material as Creative-Spiritual Practice - Hansen, Christopher Michael (Implicit religion, 2023)
This paper examines The Seth Material (1963- 1984), produced by Jane Roberts and Robert Butts, as a case study in spirit channeling as a creative-spiritual practice. It argues that the Seth phenomenon challenges creative and spiritual boundaries by blending emergent metaphysical beliefs, experimental media practices, and evolving conceptions of human and more-than-human agency. Through close analysis of the material's view of individual and collective agency, this paper situates channeling as a post-human act that reconfigures relationships between authorship, media, and spiritual practice. It also considers the Seth Material's engagement with emerging audio formats, collaborative worldbuilding, and hypertextual structure as a transmedia mode of storytelling that democratizes spiritual experience and invites distributed authorship. By framing the Seth Material as a hybrid creative- spiritual form, this paper offers new perspectives on the cultural and ontological stakes of spirit channeling in modern spiritual and artistic movements.